Loan Loss Provisioning and Economic Slowdowns : Too Much, Too Late? - Laeven, Luc; Majnoni, Giovanni (World Bank, Washington, DC, 2014)
Only recently has the debate on bank capital regulation devoted specific attention to the role that bank loan loss provisions can play as part of a minimum capital regulatory framework. Several national regulators have adopted or are planning to introduce a cyclically adjustable requirement for loan loss provisions, and the Basel Committee on Banking Supervision is considering how to provide adequate treatment to provisioning practices within a broad bank capital regulatory framework. The authors contribute to the ongoing debate by exploring the available evidence about bank provisioning practices around the world. They find that in the vast majority of cases banks tend to delay provisioning for bad loans until it is too late-when cyclical downturns have already set in-possibly magnifying the impact of the economic cycle on the income and capital of banks. Notwithstanding the considerable variation in the patterns followed by banks around the world, Laeven and Majnoni find that the size and timing of provisions tend to improve with the level of economic development.